InSAR-constrained parallel elastic finite element models for fault coseismic dislocation inversion: a case study of the 2016 MW 5.9 Menyuan earthquake - Chen, Yuhang; Hu, Caibo; Shi, Mingqian; Zhang, Huai (Frontiers in Earth Science, 2025)
The study of fault coseismic dislocation distribution is crucial for understanding fault stress release, fault sliding behavior, and surface deformation during seismic events. This knowledge is essential for engineering design and disaster prevention. Traditional seismic dislocation theories, which assume a uniform elastic semi-infinite space, fail to account for topographic relief, medium inhomogeneity in the seismic source area. In contrast, parallel elastic finite element models effectively address these complexities by accommodating geometric, material, and boundary condition variations, offering high spatial resolution and efficient computation. In this paper, we introduce a novel fault coseismic dislocation inversion method based on parallel elastic finite element simulations. We conduct inversion tests using several idealized fault models to validate our approach. Applying this method to the 2016 MW 5.9 Menyuan earthquake, we successfully invert the coseismic dislocation distributions. Our results align with previous studies and show excellent agreement with InSAR coseismic observations, thereby confirming the method’s validity. Ideal model tests demonstrate that a 10% Young’s modulus contrast across fault interfaces significantly affects coseismic dislocation inversion. Topographic relief exhibits limited influence on the coseismic dislocation inversion of the 2016 Menyuan MW 5.9 earthquake. The distinct mechanical responses of material heterogeneity and topographic effects require separate quantification, confirming our method’s viability for coseismic dislocation inversion in actual large earthquakes.